Evaluation of 209At as a theranostic isotope for 209At-radiopharmaceutical development using high-energy SPECT. (21st February 2018) - Crawford, J R; Robertson, A K H; Yang, H; Rodríguez-Rodríguez, C; Esquinas, P L; Kunz, P; Blinder, S; Sossi, V; Schaffer, P; Ruth, T J
Abstract: The development of alpha-emitting radiopharmaceuticals using 211 At requires quantitative determination of the time-dependent nature of the 211 At biodistribution. However, imaging-based methods for acquiring this information with 211 At have not found wide-spread use because of its low abundance of decay emissions suitable for external detection. In this publication we demonstrate the theranostic abilities of the 211 At/ 209 At isotope pair and present the first-ever 209 At SPECT images. The VECTor microSPECT/PET/CT scanner was used to image 209 At with a collimator suitable for the 511 keV annihilation photons of PET isotopes. Data from distinct photopeaks of the 209 At energy spectrum (195 keV (22.6%), 239 keV (12.4 %), 545 keV (91.0 %), a combined 782/790 keV peak (147 %), and 209 Po x-rays (139.0 %)) were independently evaluated for use in image reconstructions using Monte Carlo (GATE) simulations and phantom studies. 209 At-imaging in vivo was demonstrated in a healthy mouse injected with 10 MBq of free [ 209 At]astatide. Image-based measurements of 209 At uptake in organs of interest—acquired in 5 min intervals—were compared to ex vivo gamma counter measurements of the same organs. Simulated and measured data indicated that—due to the large amount of scatter from high energy (>750 keV) gammas—reconstructed images using the x-ray peak outperformed those obtained from other peaks in terms of image uniformity and spatial resolution, determined to be  <0.85 mm. 209 At imaging using the x-ray peak revealed a biodistribution that matched the known distribution of free astatide, and in vivo image-based measurements of 209 At uptake in organs of interest matched ex vivo measurements within 10%. We have acquired the first 209 At SPECT images and demonstrated the ability of quantitative SPECT imaging with 209 At to accurately determine astatine biodistributions with high spatial and temporal resolution.